THE INFLUENCE OF PRENATAL GENTLE YOGA ON THE ANXIETY OF PREGNANT WOMEN TOWARD LABOR - Indri Sari; Ita Herawati (Lembaga Pengembangan Kinerja Dosen, 2022)
Background : WHO data shows that there are around (10%) pregnant women and (13%) women who have just given birth worldwide experiencing mental disorders trauma depression. Severe anxiety during pregnancy hurts the mother-infant relationship and reduces the mother's ability to play the mother's role. Pregnancy anxiety is proven to be reduced or eliminated through physical exercise. Objective : Knowing the effect of prenatal gentle yoga on the anxiety of pregnant women facing labor. Methods : Quasi experimental with Pretest Posttest With Control Group Design. All third trimester pregnant women at BPM Mitsusylawati in October 2022 as many as 20 people with a sampling technique, namely total sampling. Results : The frequency distribution of pregnant women's anxiety in the intervention group before perinatal gentle yoga was mostly moderate anxiety (53.3%) and afterward most were not anxious 60%. In the control group mostly mild anxiety 86.7%. There is an effect of prenatal gentle yoga on the anxiety of pregnant women facing labor (p.value = 0.000). Conclusions and Suggestions: There is an effect of prenatal gentle yoga on the anxiety of pregnant women facing childbirth (p.value = 0.000). It is expected that midwives can provide midwifery care to pregnant women with perinatal gentle yoga to reduce anxiety in dealing with childbirth